The ethical dilemmas of university-industry collaborations - Kenney, Martin (Journal of business ethics, 1987)
This article examines the ethical dilemmas that can occur due to university and industry cooperative arrangements. The values that Conant (1952) and Merton (1942) ascribed to university science are used as a measure of the evolving university-industry relations in the 1980s. Examples of the types of relations being forged are discussed and possible conflicts of interest are explored. The author argues that the goals of the university are and must remain different from those of industry for the good of the entire society. The transformation of the university into a research institution for industry could result in the university not adequately training the scientists of tomorrow, and simultaneously, not discharging its duty to do basic research as it focuses on the more applied research that industry desires and funds.